2019
DOI: 10.1111/scs.12681
|View full text |Cite
|
Sign up to set email alerts
|

Maternity‐ward nurses’ kangaroo mother care attitudes and practices: implications and future challenges

Abstract: BackgroundSuccessful implementation of KMC depends on the attitudes and practices of maternity‐ward nurses. This study assessed the attitudes and practices of kangaroo mother care (KMC) by maternity‐ward nurses in the Eastern Philippines.MethodsA cross‐sectional survey design was used in the study. A convenience sample of 138 maternity‐ward nurses working in six rural health units (RHUs), two public hospitals and one private hospital. A questionnaire was used to assess the attitudes and practices of KMC by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
2
4
0
1
Order By: Relevance
“…The association of nurses’ knowledge, education, and attitudes/beliefs with SSC implementation aligned with several previous studies, which found that confidence increases when the level of knowledge increases [ 29 ] and positive attitudes toward SSC appear [ 20 ]. Education also has an important role in facilitating the faster adoption of SSC practices; when the nurses or health care providers have continuing and updated education regarding SSC practices, the implementation of SSC will also increase [ 20 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The association of nurses’ knowledge, education, and attitudes/beliefs with SSC implementation aligned with several previous studies, which found that confidence increases when the level of knowledge increases [ 29 ] and positive attitudes toward SSC appear [ 20 ]. Education also has an important role in facilitating the faster adoption of SSC practices; when the nurses or health care providers have continuing and updated education regarding SSC practices, the implementation of SSC will also increase [ 20 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 86%
“…Interpretation of nurses’ attitudes/beliefs toward SSC: Nurses have a relatively positive attitude toward SSC benefits for the newborn, which is comparable to several studies that showed a positive attitude toward SSC benefits in mother–infant bonding [ 17 , 20 , 22 , 24 ]. Although the overall score of the attitudes dimension was positive, a majority of the nurses disagreed with the statement about the effects of SSC on reducing the discomfort of minor procedures, which is in agreement with Mallet et al’s results [ 22 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…An Indian study found that most maternal–child health nurses do not practice KMC, despite a positive attitude towards the method . In the Philippines, they have a positive attitude towards KMC but poor KMC practice .…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan bir çalışmada hemşireler, annelerle etkileşim kurmak için yeterli zamanı sağlamada zorluk yaşadıklarını ve KB'nı uygularken kazara ekstübasyon konusunda bazı endişeleri olduğunu bildirmiştir (22). İran'da yapılan bir çalışmada YYBÜ'lerinde aşırı iş yükü nedeniyle KB'nın uygulanması ile zaman yetersizliği yaşadıkları bulunmuştur (21). Bu sorunların, ziyaret sürelerinin uzatılması ve hedefe yönelik yardım yaklaşımlarının uygulanmasıyla aşılabilir.…”
Section: Discussionunclassified